Determinanst of A Customer’s Decision to Choose A Murabaha Contract at Indonesian Sharia Bank - Puji Sri Kartika (Journal Of Institution And Sharia Finance, 2021)
This study aims to analyze the determinants of customers in  choosing a murabahah contract at an Islamic bank.  This type of research is research quantitatively with a population of all BSI KCP Palopo Ratulangi customers.  Taking a sample of 80 respondents using Roscoe's theory and using purposive sampling.  The method used to test the hypothesis is the classical assumption test,hypothesis testing, multiple regression testing, and test of the coefficient of determination.  The analytical tool in this study uses assistance  SPSS versions 22 and 24. From the results of data processing it shows that simultaneously variable internal factors (psychological and personal) and variables external factors (culture and demography) have a positive and significant effect on the customer's decision in choosing a murabahah contract at an Islamic bank with a significance level of 0.000.  While partially variable factor internal (psychological and personal) positive and significant effect on the customer's decision in choosing a murabahah contract at an Islamic bank with significance level of 0.004 and the value of tcount>ttable (3.823>1.991), but the variable external factors (culture and demographics) have no positive and significant effect on the customer's decision in choosing a murabahah contract at an Islamic bank with a significance level of 0.21 and tcount<ttable (1.245<1.991).